Stable isotope analysis and U-Th dating of late glacial and Holocene lacustrine sediments from central Turkey - Dean, Jonathan R. (2014)
Water is a politically sensitive resource in the Near East and water stress is increasing. It is therefore vital that there is a strong understanding of past hydrological variability, so that the drivers of change can be better understood, and so that the links between the palaeoclimate and archaeological records in this key region in the development of human civilisation can be investigated. To be of most use, this requires high resolution records and a good understanding of palaeoseasonality.